Indian Rural Marketing (Determining the Performance) - Wakchaure, Rajaram Nathji (Journal of Commerce and Trade, 2008)
An Attempt is made to study the different areas of marketing and also to determined to the performance of Indian Rural Marketing. The study best on the data pertained to 1995-96 to 2006-07. In general out of 10 years under consideration only last 5 years under consideration only last 5 years successfully years. This paper has discovered that the rural marketing strategy has to be different from urban market. A uniform marketing stategy for the total Indian Market is difficult as well as unprofitable. Market strategy as indicated above can light on some fruitful areas to be concentrated upon the create demands.